Answers

  • Brainly User
2014-10-14T18:59:46+05:30
125x raised to 3-216xraised to 3=(5x)raised to 3-(6x)raised to 3
                                                    
0
sorry, i am unable to understand this answer so please edit your answer.
actually i dont have that fonts
sry but say what is your doubt
please do this question neatly and in detail.
2014-10-14T19:32:32+05:30
125x³ - 216y³ 

= (5³)x³ - (6³)y³ 

= (5x)³ - (6y)³ → recall the previous result where: a = 5x and where: b = 6y 

= (5x - 6y).[(5x)² + (5x * 6y) + (6y)²] 

= (5x - 6y).(25x² + 30xy + 36y²)
0